Energy decay for a nonlinear wave equation of variable coefficients with acoustic boundary conditions and a time-varying delay in the boundary feedback. (January 2015) - Li, Jing; Chai, Shugen
Abstract: A variable-coefficient wave equation with acoustic boundary conditions and a time-varying delay in the boundary feedback is considered. Applying the Riemannian geometry method, we show that the decay rates of the nonlinear system with a time-varying delay are described by solutions to a first order ODE.